Arqueologia da interface: gesto, visão, memória e as regras dos jogos dos símbolos - Emmerick, Maria Christina Ennes (2008)
This work refers to some conditions that allowed the emergence of new types of human-machine interaction. Having as point of departure the audiovisual investigation of the historical process regarding the incidence of signs on bodies and their role in the creation of human-machine connections, this research aims at investigating some forms of articulation between visibilities and discourses in the production of this link by means of technical images and technical discourses related to interface computer technologies and concepts. The study of human-computer interface ponders about changes in language and perception and evaluates correlated conceptual changes in the concepts of vision, gesture and memory. The computer graphic interface, in its materiality discursive, tangible and visible, is analyzed as schemes of normative functional administration, inserted in a diagram of practices and knowledges in the new social devices of power